2006
DOI: 10.1093/nar/gkl909
|View full text |Cite
|
Sign up to set email alerts
|

Purine analog substitution of the HIV-1 polypurine tract primer defines regions controlling initiation of plus-strand DNA synthesis

Abstract: Despite extensive study, the mechanism by which retroviral reverse transciptases (RTs) specifically utilize polypurine tract (PPT) RNA for initiation of plus-strand DNA synthesis remains unclear. Three sequence motifs within or adjacent to the purine-rich elements are highly conserved, namely, a rU:dA tract region immediately 5′ to the PPT, an rA:dT-rich sequence constituting the upstream portion of the PPT and a downstream rG:dC tract. Using an in vitro HIV-1 model system, we determined that the former two el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 47 publications
1
17
0
Order By: Relevance
“…Despite extensive mutagenesis analysis (Rausch and Le Grice 2007), the structural basis for resistance of PPT-containing RNA/DNA hybrids to RNase H-mediated cleavage remains unclear. However, structural studies that combined mass spectrometry with NMR , raise the possibility that the PPT could be targeted by small molecules designed to antagonize its selection or removal from nascent (+) DNA.…”
Section: Protein Synthesis and Ribosomal Frameshifting: A Delicate Bamentioning
confidence: 99%
“…Despite extensive mutagenesis analysis (Rausch and Le Grice 2007), the structural basis for resistance of PPT-containing RNA/DNA hybrids to RNase H-mediated cleavage remains unclear. However, structural studies that combined mass spectrometry with NMR , raise the possibility that the PPT could be targeted by small molecules designed to antagonize its selection or removal from nascent (+) DNA.…”
Section: Protein Synthesis and Ribosomal Frameshifting: A Delicate Bamentioning
confidence: 99%
“…There are no base contacts with positions −4 or −7, but there are phosphate contacts from −4 to −9 in the DNA strand with the RNase H primer grip region. Using model substrates and purified enzyme, positions −2 and −4 are essential for correct cleavage of the PPT (Pullen et al, 1993) and substitutions at positions +1, −2, and −4 of the PPT substantially decrease generation of the PPT primer (Rausch and Le Grice, 2007). In other studies examining the recognition and cleavage of the PPT by HIV-1 RNase H, the effects of mutations in the PPT and in the primer grip region of the RNase H domain have been assessed both in vitro and in vivo Julias et al, 2004;McWilliams et al, 2006;Jones and Hughes, 2007).…”
Section: Generation Of Ppt Primermentioning
confidence: 99%
“…A variety of studies have identified the nucleotide positions within the PPT that are critical for proper cleavage and although some of these overlap with the more general preferences for internal cleavage, other positions do not. Thus, for proper PPT primer generation by M‐MLV RNase H, positions −1, −2, −4, −5, −6, −7, −10 and −11 are important [51,94,95], whereas positions +1, −2, −4, −5 and −7 have been found to be critical for HIV‐1 PPT primer formation [38,40,89,96–98].…”
Section: Roles Of Rnase H In Reverse Transcriptionmentioning
confidence: 99%